Exploring the mechanical and tribological properties of AlCrFeNiTi high-entropy alloy fabricated by mechanical alloying and spark plasma sintering - Nagarjuna, Cheenepalli; Dewangan, Sheetal Kumar; Lee, Hansung; Lee, Kwan; Ahn, Byungmin (Vacuum, 2023)
The present study explores the mechanical and tribological properties of AlCrFeNiTi high entropy alloy (HEA) processed by mechanical alloying (MA) and spark plasma sintering (SPS). The results show the formation of a single-phase BCC structure after MA at 30 h, and after SPS a single BCC phase decomposed into dual BCC1; AlNi2Ti, and BCC2; CrFe phases. The maximum hardness of ∼960 ± 10 HV and ultimate compressive strength of ∼1650 ± 50 MPa were achieved. The nano hardness of ∼951 ± 21 HVIT and the elastic modulus of ∼256 ± 22 GPa were observed. Further, the ball-on-disc dry sliding tests were performed to study the friction and wear behavior of HEA at different loads and sliding velocities. The average coefficient of friction is about 0.3 for all the applied loads, suggesting no significant difference with load. In contrast, the average coefficient of friction slightly increased from 0.23 to 0.27 with increasing velocity. The specific wear rate increased from 2.66 to 5.06 × 10−6 mm3/Nm and 2.2 to 3.61 × 10−6 mm3/Nm with increasing load from 5 to 15 N and velocity from 0.08 to 0.12 m/s, respectively. Moreover, a transition in wear mechanism was observed from abrasive to oxidative and delamination wear with increasing load and sliding velocity.
Keywords: BCC phase; Coefficient of frictions; High entropy alloys; Maximum hardness; Mechanical and tribological properties; Single phasis; Sliding velocities; Spark-plasma-sintering; Tribological properties; Ultimate compressive strength; High entropy alloy; Mechanical properties; Microstructure; Powder metallurgy; Tribological properties